El inglés como segunda lengua: acceso y oportunidad en el sistema universitario - Yaranga Hernández, Mayra (2013)
Through this article, which is searching to go in depth the idea abouta foreign language knowledge as English is needed for the modemprofessional, that idea usually does not have a specific support and fallswithin cliché category. That’s why two aspects will be develop withinthe context of university higher education: the English learning necessityunderstood as access and the potential did not use of the internationalacademic exchanges for learning to life in the global community. In thatway, is expecting to give a clearer and specific view about English learningimplications within contemporary university education context.